English Word Learning Using Intelligent Massive-Scale Big Data Mining Technique - Lei Jin (Applied Bionics and Biomechanics, 2022)
Big data technique has become a scientific force driving disruptive innovation and change in the education system and the entire field, including English word learning, which will undergo profound mechanism changes under the impetus of this trend. The reform of basic English education evaluation in the new era empowered by big data is an inevitable choice to get rid of the chronic problems of the “five-only” education evaluation and to implement the education that builds morality as well as learners’ satisfaction. Traditional classroom teaching is combined with educational information technology to build a smart campus for English education. And data mining hidden educational information and rules are obtained to meet the requirements of students’ personalized learning and other demands. However, the reality is faced with the alienation of the concept of big data in English word learning. Data mining is a very important thinking tool and learning tool, which can help students better learn basic English knowledge, memorize basic words, and improve learning effect. At the same time, it has the effect of cultivating divergent thinking and systematic learning. The foundation of English learning in high school is vocabulary. In order to help students better memorize English vocabulary, teachers can apply mind map associative memory method to implement teaching. In order to solve the problem, this paper proposes the English value concept, constructs a basic education evaluation concept empowered by big data, and eliminates teachers’ concerns about technical ability. We also improve the intellectual support for evaluation reform and reasonably build a data resource platform to meet students’ comprehensive quality evaluation demands. The method accurately conducts the big data evaluation to drive suggestions such as the reconstruction of educational evaluation system.